The co‐occurrence and correlates of anxiety disorders among adolescents with intermittent explosive disorder. Issue 6 (24th July 2018) - Galbraith, Todd; Carliner, Hannah; Keyes, Katherine M.; McLaughlin, Katie A.; McCloskey, Michael S.; Heimberg, Richard G.
Abstract : We examined the lifetime prevalence of anxiety disorders (ADs) among adolescents with lifetime intermittent explosive disorder (IED), as well as the impact of co‐occurring ADs on anger attack frequency and persistence, additional comorbidity, impairment, and treatment utilization among adolescents with IED. IED was defined by the occurrence of at least three anger attacks that were disproportionate to the provocation within a single year. Data were drawn from the National Comorbidity Survey‐Adolescent Supplement ( N  = 6, 140), and diagnoses were based on structured lay‐administered interviews. Over half (51.89%) of adolescents with IED had an AD, compared to only 22.88% of adolescents without IED. Compared to adolescents with IED alone, adolescents with IED and comorbid ADs: (a) were more likely to be female; (b) reported greater impairment in work/school, social, and overall functioning; (c) were more likely to receive an additional psychiatric diagnosis, a depressive or drug abuse diagnosis, or diagnoses of three or more additional disorders; and (d) had higher odds of receiving any mental/behavioral health treatment as well as treatment specifically focused on aggression. Adolescents with IED alone and those with comorbid ADs did not differ in the number of years experiencing anger attacks or the highest number of anger attacks in a given year. ADs frequently co‐occur with IED and are associated with elevated comorbidity and greater impairment compared to IED alone. Gaining a better understanding of this comorbidity is essential for developing specialized and effective methods to screen and treat comorbid anxiety in adolescents with aggressive behavior problems.